2009
DOI: 10.1002/pro.148
|View full text |Cite
|
Sign up to set email alerts
|

Mistic: Cellular localization, solution behavior, polymerization, and fibril formation

Abstract: Mistic represents a family of unique membrane-associating proteins originally found in Bacillus subtilis (M110). As a fusion partner, it has been shown to assist overexpression of foreign integral membrane proteins in E. coli. We have expressed shorter Mistic homologs from other Bacillus species and surprisingly, unlike M110, found them abundant in the cytoplasm. These Mistic homologs including the corresponding shorter sequence (amino acids 27 through 110 of M110) exist as multimeric assemblies in solution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Moreover, the soluble form of the M110-GFP fusion was also observed in L. lactis (Fig. 3), which was in agreement with Mistic behaviour in E. coli (Dvir et al, 2009). …”
Section: Mistic Behaviour In L Lactis By Fluorescence Detection Of Msupporting
confidence: 85%
“…Moreover, the soluble form of the M110-GFP fusion was also observed in L. lactis (Fig. 3), which was in agreement with Mistic behaviour in E. coli (Dvir et al, 2009). …”
Section: Mistic Behaviour In L Lactis By Fluorescence Detection Of Msupporting
confidence: 85%
“…A truncated version of Mistic shorter by 25 residues -M110 -expresses primarily in the bacterial membrane [72]. Interestingly, shorter Mistic proteins maintain comparable levels of expression as M110 even though they are soluble in the presence of detergents and are localized mainly to the cytoplasm [75]. Mistic's mecha-Biotechnol.…”
Section: Misticmentioning
confidence: 99%
“…Remarkably, the shorter Mistic proteins are significantly more soluble than M110 when expressed independently in E. coli , all of which are mainly localized in the cytoplasm and do not require detergent for solubility [16]. The rank order of solubility is as follows, M1~M3 > M2 >> M4 (>M110) such that M4 interacts the most strongly with the membrane similar to the insoluble M110 except that it exists in the cytoplasm as well.…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of shorter Mistic orthologs provided new opportunities for optimizing expression of IMPs, given that they were all shown to serve as fusion partners for expression of IMPs at the bacterial membrane [12]. Surprisingly, it was recently shown that, unlike M110, the shorter Mistic proteins are soluble in the absence of detergents and they are mainly cytoplasmic, but show significantly varying membrane association propensities [16]. In accordance with previous suggestion on the independent ability of Mistic to facilitate membrane expression of IMPs, that study indicates that isolated Mistic proteins may spontaneously insert into the membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation